Au concentration‐dependent quenching of Raman 2D peak in graphene. (25th January 2017) - Ranjan, Pranay; Tulika,; Laha, Ranjit; Balakrishnan, Jayakumar
Abstract : We investigate the effect of sputtered gold nanoclusters (AuNCs) on the Raman spectra of graphene. The two prominent Raman peaks of graphene – 2D and G – show drastically different behaviour with AuNC introduction. The Raman 2D peak intensity decreases with gold coverage and finally is quenched for moderate gold nanoparticle coverage, while the G peak shows a AuNC size‐dependent enhancement in peak intensity. The quenching of the 2D peak is attributed to the hybridization of graphene's 2pz orbital with the 5d orbitals of Au. The G peak enhancement is due to the surface‐enhanced Raman scattering induced by the surface plasmons created in the AuNC by the incident laser beam (He–Ne laser, wavelength = 632.8 nm). The existence of surface plasmons is independently confirmed by UV‐visible spectrophotometry measurements. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We investigate the effect of sputtered gold nanoclusters (AuNCs) on the Raman spectra of graphene. The Raman 2D peak intensity decreases with gold coverage and finally is quenched for moderate gold nanoparticle coverage, while the G peak shows a AuNC size‐dependent enhancement in peak intensity. The quenching of the 2D peak is attributed to hybridization of graphene with Au. The G peak enhancement is due to the surface‐enhanced Raman scattering due to AuNC.